Low plasma carnosinase activity promotes carnosinemia after carnosine ingestion in humans - Everaert, Inge; Yard, Benito A.; Hauske, Sibylle J. (American journal of physiology. Renal physiology, 2012)
A polymorphism in the carnosine dipeptidase-1 gene (CNDP1), resulting in decreased plasma carnosinase activity, is associated with a reduced risk for diabetic nephropathy. Because carnosine, a natural scavenger/suppressor of ROS, advanced glycation end products, and reactive aldehydes, is readily degraded in blood by the highly active carnosinase enzyme, it has been postulated that low serum carnosinase activity might be advantageous to reduce diabetic complications. The aim of this study was to examine whether low carnosinase activity promotes circulating carnosine levels after carnosine supplementation in humans. Blood and urine were sampled in 25 healthy subjects after acute supplementation with 60 mg/kg body wt carnosine. Precooled EDTA-containing tubes were used for blood withdrawal, and plasma samples were immediately deproteinized and analyzed for carnosine and β-alanine by HPLC. CNDP1 genotype, baseline plasma carnosinase activity, and protein content were assessed. Upon carnosine ingestion, 8 of the 25 subjects (responders) displayed a measurable increase in plasma carnosine up to 1 h after supplementation. Subjects with no measurable increment in plasma carnosine (nonresponders) had ∼2-fold higher plasma carnosinase protein content and ∼1.5-fold higher activity compared with responders. Urinary carnosine recovery was 2.6-fold higher in responders versus nonresponders and was negatively dependent on both the activity and protein content of the plasma carnosinase enzyme. In conclusion, low plasma carnosinase activity promotes the presence of circulating carnosine upon an oral challenge. These data may further clarify the link among CNDP1 genotype, carnosinase, and diabetic nephropathy.
Gesehen am 28.11.2018